Strain-encoded cardiac magnetic resonance imaging: a new approach for fast estimation of left ventricular function - Lapinskas, Tomas; Zieschang, Victoria; Erley, Jennifer; Stoiber, Lukas; Schnackenburg, Bernhard; Stehning, Christian; Gebker, Rolf; Patel, Amit R.; Kawaji, Keigo; Steen, Henning; Zaliunas, Remigijus; Backhaus, Soeren J.; et al. (Bmc Cardiovascular Disorders, 2019)
Background: Recently introduced fast strain-encoded (SENC) cardiac magnetic resonance (CMR) imaging (fast-SENC) provides real-time acquisition of myocardial performance in a single heartbeat. We aimed to test the ability and accuracy of real-time strain-encoded CMR imaging to estimate left ventricular volumes, ejection fraction and mass. Methods: Thirty-five subjects (12 healthy volunteers and 23 patients with known or suspected coronary artery disease) were investigated. All study participants were imaged at 1.5 Tesla MRI scanner (Achieva, Philips) using an advanced CMR study protocol which included conventional cine and fast-SENC imaging. A newly developed real-time free-breathing SENC imaging technique based on the acquisition of two images with different frequency modulation was employed. Results: All parameters were successfully derived from fast-SENC images with total study time of 105 s (a 15 s scan time and a 90 s post-processing time). There was no significant difference between fast-SENC and cine imaging in the estimation of LV volumes and EF, whereas fast-SENC underestimated LV end-diastolic mass by 7%. Conclusion: The single heartbeat fast-SENC technique can be used as a good alternative to cine imaging for the precise calculation of LV volumes and ejection fraction while the technique significantly underestimates LV end-diastolic mass.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac magnetic resonance; Cine imaging; Left ventricular function; Strain-encoded imaging